Instances of Flouting of the Conversational Maxims by Della & Jim in O. Henry’s The Gift of the Magi (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Pragmatics as defined by Kreidler (2009) is a study about people’s “ability to derive meaning from specific kinds of speech situation” and also to arrive at ‘an interpretation.The cooperative principle lays down norms for people to interact with one another. Mutual cooperation is a necessity among speakers. Building upon Gricean Maxims(1975) Fasold and Connor (2006) and Paltridge (2006) argue that the maxims rely on the addressee’s assumption in making a sense of what the speakers say. The assumption which is made by the addressee/s should be rational and cooperative to create the effective communication. Usually people do not obey the maxims. They tend to violate, flout, infringe or opt out the maxims. This research focuses on the flouting of maxims by the main characters Jim and Della in O.Henry’s The Gift of the Magi. This study uses descriptive Qualitative Method to find out the number of utterances  the number of floutings and it tries to decipher the strategies and reasons behind the floutings. The study identified that 96.87% of utterances are flouted. It also found that all the maxims are flouted. All the characters in the short story flouted the maxims.